16O(n,p)16N reaction cross sections around 14 MeV - Subasi, M; Gültekin, E; Reyhancan, IA; Özbir, Y; Tarcan, G; Sirin, M; Erduran, MN (AMER NUCLEAR SOCIETY, 2000)
The (n,p) reaction cross sections of O-16 in the neutron energy range from 13.6 to 14.9 MeV were measured by the activation method. The gamma-ray counting technique was applied, and the cross sections were determined relative to the Al-27(n,p)Mg-27 reaction cross sections. The neutrons were produced via the H-3(d, n)He-4 reaction on a SAMES T-400 neutron generator, and the induced gamma activities were measured by a high-purity germanium (HPGe) detector. The efficiency calibration of the HPGe detector for gamma-ray energies above 6 MeV was determined by means of gamma rays emitted from the decay of Be-11. An automated fast sample transport system was combined with the neutron generator in order to carry out the measurements in cyclic mode. The experimental method is described and the sources of systematic errors are discussed. The results obtained are compared with the experimental data in the available literature and recent evaluations.
Keywords: Nuclear Science & Technology